Development of sensor for monitoring the integrity of the lubrication system of heavy duty pumps in nuclear reactors - Vidhatri, M. M. Shri; Sivaramakrishna, M.; Mathur, Vivek; Chitrakkumar, S. (2022 2nd International Conference on Emerging Frontiers in Electrical and Electronic Technologies (ICEFEET), 2022)
In Prototype Fast Breeder Reactor(PFBR), heavy secondary sodium rotary pumps are provided with oil pots to collect the lubricating oil of the cooling system in case of minute leaks. These leaks need to be detected as early as possible. The Innovative sensor section(ISS) has developed a sensor with the electronics to detect the oil when it reaches a threshold level (5mm). The sensor can work accurately even above 100°C temperature. The added features of this sensor are it's robust nature and fail-safe model with very few random errors. The sensor has no moving or heating parts and a fast response time.